2021
DOI: 10.18280/ijsdp.160111
|View full text |Cite
|
Sign up to set email alerts
|

Societal Green Economy and its Impact on Sustainable Development

Abstract: The research uses a descriptive experimental methodology based on the study of the experiences of countries to benefit from them as an applied method of transition to the green economy in the project of a new city in Samawah. The use of analyzing developmental potentials method, the SWOT model and the spatial interaction of the reality of the situation Using modern GIS technologies have also been employed. The first section dealt with the conceptual framework of the green economy and its importance and compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
3
0
2
Order By: Relevance
“…They argue that through their transformation they are positioned to make better contributions to the national economy. As a result of this, it has been observed that the Nigerian government has on several occasions provided soft loans to finance business transformation and sustainability [ 30 , 31 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…They argue that through their transformation they are positioned to make better contributions to the national economy. As a result of this, it has been observed that the Nigerian government has on several occasions provided soft loans to finance business transformation and sustainability [ 30 , 31 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another goal of this initiative is the construction of urban facilities that are friendly to people and the environment. One of the examples of its implementation is the Smart Dubai program, based on digital transformation [6]. The next goal is to manage water and energy sustainably.…”
Section: The United Arab Emirates Green Economymentioning
confidence: 99%
“…The construction of primary indicators uses the theoretical analysis method, which is mainly to clarify the connotation and theoretical basis of green economy through theoretical learning and data collection and analysis, and determine the primary indicators in combination with relevant literature indicators. The green economy index system should have three important functions: first, it can comprehensively reflect the level and development of all aspects of green economy; second, be able to monitor the development speed and trend of each aspect in a period of time and grasp the latest state; third, the analysis of the evaluation results can provide direction for the future government macro management, find specific problems and provide basis for suggestions [16].…”
Section: Green Industry Development Model Evaluation Indicators Of Gr...mentioning
confidence: 99%